Republic of Poland : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2000)
Poland is placed high among the most successful transition economies owing to its strong macroeconomic and structural policies. Executive Directors commended this development, and stressed the need to maintain monetary and fiscal policies. They appreciated the tax and pension systems, banking supervision and regulatory framework, and industrial restructuring and privatization. They welcomed the policymakers' focus on ensuring progress toward membership in the European Union accession. They agreed that the country's statistical base is adequate for surveillance, and encouraged the authorities to improve the quality of macroeconomic data.